Behaviour of carbon fibre reinforced polymer plate under tensile load - Mohd. Sam, Abdul Rahman (Penerbit UTM, 2008)
Strength and long-term durability of reinforced concrete structures are the most important criteria to be considered in the design process. However, many reports indicated that quite a number of reinforced concrete structures around the world are facing either strength or durability problem. The problem related to strength is may be due to the changes on the load to be carried by the structures in which in some instances the structures may be subjected to carry higher load than the initial design due to changes in their current use. Thus, it is sometimes more economical to upgrade structures rather than rebuilding them, especially when rapid, effective and simple strengthening methods are available (Balendran et.al. 2001). Nowadays, the strengthening of existing structures using Fibre Reinforced Polymer (FRP) materials are fairly common due to the advancement in the technology. FRP is a combination of continuous fibres embedded in resin matrix. The principle of strengthening method using FRP materials is relatively simple where the FRP is bonded to the concrete member using adhesive. Among other advantages offered by this strengthening technique include ease of application and elimination of special anchorages needed in post-strengthening method (Saadatmanesh, 1994). Study on under-reinforced reinforced concrete beam strengthened with Glass Fibre Reinforced Polymer (GFRP) plate shows the flexural behaviour of the beam was improved (Mohd. Sam et.al. 2002). Since the properties of FRP materials are generally different compared to steel, their characteristics under tension need to be understood. This is important to ensure the safety of the structures. This paper presents the study on the tensile behaviour of CFRP plate that generally being used in the strengthening of reinforced concrete structures. The sample preparation, ultimate load, stress-strain behaviour, and mode of failure of the samples were thoroughly studied.